New multifunctional dietary supplements based on raw carrot - Bessarab, Alexander; Bandurenko, Galina; Levkivska (Muzika), Tetiana (My University, 2013)
In the work was scientific justification of an integrated approach to processing carrot to get two carotene-compound multifunctional food additives in dry and liquid form. У роботі був науково обгрунтуваний комплексний підхід до переробки моркви з отриманням двох каротиновмісних багатофункціональних харчових добавок у сухому і рідкому вигляді.
Keywords: carrot; β-carotene; food аdditives; морква; β-каротин; харчові добавки; кафедра технології консервування